2009
DOI: 10.1007/s11430-009-0038-7
|View full text |Cite
|
Sign up to set email alerts
|

The Early Jurassic magmatism in northern Guangdong Province, southeastern China: Constraints from SHRIMP zircon U-Pb dating of Xialan complex

Abstract: This paper reports SHRIMP zircon U-Pb ages of 196±2 Ma for granite, and 195±1 Ma for gabbro from theXialan complex in the Meizhou area, northern Guangdong Province. These results shed new light on the calm stage of magmatic activity in southeastern China during 200-180 Ma, and revealed that the back-arc extension induced by the subduction of the western Pacific plate may have begun at 195 Ma at least. Field observation on the fresh outcrops allows us to recognize some features formed by magma mixing. A part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…They are usually grouped into two main groups, that is, Jurassic rocks in inland regions and Cretaceous rocks along the coastal provinces, but precise geochronological studies of many intrusions have not confirmed the temporal-spatial distribution (e.g., Zhou et al, 2006aZhou et al, , 2006bZhou et al, , 2007 Fig. 8a; e.g., Li et al, , 2009cWang et al, 2004aWang et al, , 2006aWong et al, 2009;He et al, 2010;Jiang et al, 2006Jiang et al, , 2009Jiang et al, , 2011, with the exception of several intrusions yielding the ages of 190-195 Ma (e.g., Qiu et al, 1999Zhou et al, 2005;Huang et al, 2008;Yu et al, 2009bYu et al, , 2010bZhu et al, 2010). Similar patterns are also given by the Mesozoic A-type granites and syenites in the eastern SCB (Fig.…”
Section: Jurassic-cretaceous Magmatismmentioning
confidence: 99%
See 2 more Smart Citations
“…They are usually grouped into two main groups, that is, Jurassic rocks in inland regions and Cretaceous rocks along the coastal provinces, but precise geochronological studies of many intrusions have not confirmed the temporal-spatial distribution (e.g., Zhou et al, 2006aZhou et al, , 2006bZhou et al, , 2007 Fig. 8a; e.g., Li et al, , 2009cWang et al, 2004aWang et al, , 2006aWong et al, 2009;He et al, 2010;Jiang et al, 2006Jiang et al, , 2009Jiang et al, , 2011, with the exception of several intrusions yielding the ages of 190-195 Ma (e.g., Qiu et al, 1999Zhou et al, 2005;Huang et al, 2008;Yu et al, 2009bYu et al, , 2010bZhu et al, 2010). Similar patterns are also given by the Mesozoic A-type granites and syenites in the eastern SCB (Fig.…”
Section: Jurassic-cretaceous Magmatismmentioning
confidence: 99%
“…4). One is a roughly east-westerly trending volcanic zone along the Nanling Range from southern Hunan (e.g., Daoxian, Ningyuan and Changchengling) through southern Jiangxi (e.g, Linjiang-Dongkeng and Huichang) and finally to southeastern Fujian (e.g., Pankeng and Meilin) (e.g., Jiangxi BGMR, 1984;Zhao et al, 1998;Chen et al, 1999Chen et al, , 2002aLi et al, 2003Li et al, , 2004Wang et al, 2003bWang et al, , 2005cWang et al, , 2005bDeng et al, 2004a;Xie et al, 2005a;Zhou et al, 2005Zhou et al, , 2006aZhu et al, 2005;Chen et al, 2008a;Yu et al, 2009bYu et al, , 2010bHe et al, 2010). These rocks formed in the early-middle Jurassic (dominantly at , and are compose of 45% basaltic and 50% rhyolitic rocks along with a small amount of andesite (e.g., Zhao et al, 1998;Chen et al, 1999Chen et al, , 2002aWang et al, 2003bWang et al, , 2005b.…”
Section: Jurassic-cretaceous Magmatismmentioning
confidence: 99%
See 1 more Smart Citation
“…160 Ma and most of these granitic rocks are distributed along the southern inland area of a E-W trending Nanling Range and the south part of the Shi-Hang Zone (e.g. Yu et al, 2009Yu et al, , 2010, and see review by Chen et al, 2008;Jiang et al, 2008). In contrast, the Cretaceous magmatism is dominated by high-potassium I-type and some A-type granites and felsic volcanic rocks.…”
Section: Tectonic Implicationsmentioning
confidence: 99%
“…According to Yu et al (2009), the Xialan complex is composed of felsic intrusive rocks and gabbros. The different contact correlation are visible between them, such as the gradual transition signature and embayed or irregular contact.…”
Section: The Xialan Complexmentioning
confidence: 99%